POST-DISSECTION THORACO-ABDOMINAL ANEURYSMS: RESULTS OF OPEN AND ENDOVASCULAR REPAIR - Gouveia e Melo, Ryan (2021)
Introduction/Objectives: Repair of post-dissection thoraco-abdominal aortic aneurysms (PD-TAAA) is a complex challenge. Choosing the correct approach to manage these aneurysms is not straightforward as both open and endovascular strategies are valid. Our aim was to analyze and compare the results of PD-TAAA treated by endovascular or open surgery. Methods: A seven-year (January-2013 and May-2020) single-center retrospective cohort study of patients with PD-TAAA treated by endovascular (group-1) or open (group-2) surgery was conducted. Primary outcome was in-hospital mortality. Secondary outcomes were organ lesion, in-hospital infections, length of stay (LOS), endoleaks, branch occlusions, re-interventions and mortality during follow-up. Results: Twenty-one patients (15-men) were treated: 8 in group-1 and 13 in group-2. The mean age was lower in group-2 [68 (SD:11) versus 48 (SD:12), p=0.004]. Three patients had connective tissue disease (CTD). Group-1 patients had a higher ASA score (p<0.001). In group-1, debranching and TEVAR were performed in 2 patients and custom-made fenestrated/ branched-endografts were used in 6. In group-2, there was one thoracic aorta interposition graft and reconstruction involving the visceral arteries ocurred in 12 patients. Seven cases were operated using the Crawford technique with visceral patch, and branched grafts were used in 3 patients with CTD. Intercostal arteries were revascularized in 5 patients. In-hospital mortality was 12% (1 patient) in group-1 and 15% (2 patients) in group-2, LogRank=0.9. The LOS was longer in group-2 (p=0.033), and there was a tendency for a longer stay in intensive care unit in this group. No difference was observed in spinal cord ischemia, acute kidney injury or re-interventions. There were more post-operative infections in group-2 (12% versus 69%, p = 0.017). During follow-up [median 15 months (IQR:55)], there was no mortality after discharge. In group-1, 14% had type-II-endoleaks, without aneurysmal sac dilation. Branch permeability during follow-up was 100% in group-1 and 95% in group-2, LogRank=0.3. Conclusion: Endovascular and open surgery of PD-TAAA allowed treatment of a wide variety of patients in this cohort. Patients treated by the endovascular surgery were older and had higher surgical risk but without repercussions on the outcomes. Open surgery was associated with longer hospital stay and more postoperative complications.